STABILITAS FOTOOKSIDASI MINYAK GORENG SAWIT YANG DIFORTIFIKASI DENGAN MINYAK SAWIT MERAH - Nuri Andarwulan; Gema Noor Muhammad; Afifah Z. Agista; Satrya Dharmawan; Dwi Fitriani; Ayu C. Wulan; Desty G. Pratiwi; Winiati P. Rahayu; Drajat Martianto; Purwiyatno Hariyadi (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2016)
Deterioriation of palm oil fortified with vitamin A and provitamin A could be caused by the presence of oxygen and light exposure. The purpose of this study was to determine the effect of the initial peroxide value (PV) in palm oil (1.99, 3.98, and 9.95 meq O2/kg oil) and light intensity (15000, 10000, and 5000 lux) on the rate of oxidation and the shelf life of palm oil fortified with Red Palm Oil (RPO) equal to 45 IU vitamin A. The RPO contained β-carotene as provitamin A in the amount of 504.67 ppm. The PV and free fatty acid (FFA) content were observed as the parameters of oil deterioriation during storage. The results showed that the rate of PV was influenced by light intensity, while the rate of FFA formation were more influenced by the amount of initial PV in the oil. Based on the palm oil standard quality for PV (SNI 7709: 2012), the shelf life of palm oil with the lowest initial PV at ambient temperature was 9.5 days, while that with the highest PV was 1.32 hours. The deterioration rate of RPO fortified palm oil due to light exposure was also compared with its deterioration rate due to heat and the deterioration rate of palm oil fortified with vitamin A. The shelf life of vitamin A fortified palm oil stored in the dark was 90.67 days, while RPO fortified palm oil was 68.12 days. This shelf life results showed that RPO had a potency as provitamin A fortificant for palm oil as long as it is stored in a closed container in the dark.